IMPLEMENTASI UANG MUKA PEMBIAYAAN KENDARAAN BERMOTOR SEBESAR 20% DI PT. FINANSIA MULTI FINANCE (KREDIT PLUS) BERDASARKAN PASAL 17 AYAT (1) HURUF A PERATURAN OTORITAS JASA KEUANGAN NOMOR 29 TAHUN 2014 - Meyer, Edward John; Bachtiar, Maryati; ', Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
In this modern era of two-wheel motor vehicles is not difficult again for all of society. Access to motor vehicles diinginkanpun not difficult even made easy by the many financing companies do promotions to attract people in order immediately to get motorists who want to deliver advertisements, brochures or flyers motors with a new type that attract people to buy the vehicle. In providing soft loans and advances are very cheap affordable for the entire community both economic and upper or middle class. In an advance payment are set out in Article 17 paragraph 1 letter a POJK (Regulation of the Financial Services Authority) Number 29 Year 2014 About Advances Financing of Motor Vehicles, amounting to 20% (twenty percent) of the selling price of the vehicle concerned. But PT. Finansia Multi Finance (Credit Plus) does not implement the regulationThe purpose of writing this essay, namely; First, to know how is the execution of advance financing of motor vehicles by 20% in PT. Finansia Multi Finance under Article 17 paragraph (1) letter a Regulation of the Financial Services Authority, No. 29 of 2014. Secondly, to know the constraints faced by PT. Finansia Multi Finance (Credit Plus) in the implementation of credit advances at a minimum of 20% towards the purchase of motor vehicles.This type of research is a sociological research, because the authors of the study on the effectiveness of the laws in force. This research was conducted at the office of PT. Finansia Multi Finance (Credit Plus) while the sample population is a whole party related to the issues examined in this study, the data source used, primary data, secondary data and data tertiary data collection techniques in this study with interviews and studies literature.From the research problem there are two main things that can be inferred. First, many low-income consumers sehigga difficult PT. Finansia Multi Finance to implement the regulation. Second, obstacles in determining a minimum down payment of 20% is still very high both for consumers and PT. Finansia Multi Finance. Advice writer, first, to rethink the establishment of a minimum down payment of 20% for the Financial Services Authority. Second, make a well in the regulation must be submitted to the parties concerned with these regulations as well as to consumers PT. Finansia Multi Finance in order to always be on time to meet its obligations, namely to pay the monthly installments as agreed by both parties.Keywords: Implementation - Vehicle Financing - Financial Services Authority No. 29 of 2014